Marriage norms and fertility outcomes in developing countries - Aniema Atorudibo (University of Kent, School of Economics, 2021)
Recent UN data show that the lifetime fertility of women in developed countries has fallen below 2.1 live births. By contrast, fertility rates in most developing countries have remained quite high despite falling mortality rates. This paper examines the effect of culture on fertility outcomes in developing countries, using the norms of premarital sexual behaviour as a measure of culture. Three types of norms are identified viz., the emphasis on female early marriage, the emphasis on female virginity at marriage, and weakly censuring premarital sexual behaviour. These differences in premarital rules are a source of identifying variation in the age at first birth and the number of children. Using a sample of women aged 15 to 49 from Africa and Turkey, the study shows that premarital sexual norms significantly affect the age at first birth and the number of children per woman. It finds that the cultural emphasis on early marriage significantly lowers a woman's age at first birth while it raises her fertility level relative to the culture which weakly censures female premarital sexual relations. Conversely, the emphasis on female virginity at marriage increases the age at first birth and lowers fertility relative to the comparison group.
Keywords: 330; Fertility; Adolescent fertility; Premarital norms; Cultural preferences